Children at risk: an initial comparison of child pedestrian traffic collisions in Santiago, Chile and Seoul, South Korea - Blazquez, Carola; Lee, Jae Seung; Zegras, Christopher; Jara, Emilio (Congreso Chileno de Ingeniería de Transporte, 2013)
We examine pedestrian traffic collisions involving children in Santiago de Chile and Seoul, Korea in 2010-2011. Descriptive statistics suggest that children in Seoul have a higher risk of being involved in accidents than their counterparts in Santiago; although in Seoul a higher share of children escape without injury than in Santiago. Both cities have temporal patterns unsurprisingly consistent with the school day and school years; although Seoul has slightly lower winter rates. Exploratory regression models reveal varying relationships between different measures of the built form and transportation system and accident density and risk, although further model development is needed.